Supply Chain Transformation : Practical Roadmap to Best Practice Results. - Sherman, Richard (New York : Wiley, 2012)
Achieve best practices in supply chain management Much is being written about global supply chain and sourcing options emerging in today's marketplace. Transforming supply chain management to achieve operations excellence is a mandate for many companies globally. Supply Chain Transformation walks you through this potentially difficult process and gets you started on the journey. Much more than just a how-to book, it's a why-to book that is as compelling for any business person as it is for supply chain management professionals. This book provides an invaluable road map to companies looking to.
So, How Do We Get It?Understanding the Demand Performance Structure; You Can't Manage What You Can't Measure; Process Types That Drive the Demand Performance Structure; What Keeps the CEO and CFO Up at Night?; How Does Operations (Supply Chain) Excellence Impact the Income Statement and Balance Sheet to Drive Return on Invested Capital?; Notes; Chapter 8: Technology Drives the Waves of Change; Scanning the Horizon for Technology Developments; What Emerging Technologies Are Likely to Impact the Supply Chain?; How Does Technology Impact the Organization?
Print version record.
Includes bibliographical references and index.
John Wiley and Sons
Keywords: Business logistics; Logistics; Logistique (Organisation); Logistique; Business logistics; Logistics; Logistiek (economie); Ketenbeheer (logistiek)